The Role of Essential Oils on Sleep Quality and Other Sleep-related Issues: Evidence from Clinical Trials - Sivamaruthi, Bhagavathi Sundaram; Kesika, Periyanaina; Sisubalan, Natarajan; Chaiyasut, Chaiyavat (Mini Reviews in Medicinal Chemistry, 2025)
Essential oils (EOs) are a volatile mixture of bioactive compounds extracted from aromatic plants. The composition of EOs varies, which majorly depends on the extraction methods and plant parts. Aromatherapy using EOs has been reported for its several beneficial effects in humans. Aromatherapy is considered a complementary and/ or adjuvant therapeutic approach for treating several illnesses, especially to improve mental health and well-being. The incidence of sleep disorders, specifically insomnia, is nowadays increased, possibly due to urbanization and lifestyle. The studies showed that EOs-based treatments using lavender EO, bergamot EO, cinnamon EO, and rosemary EO (alone or in combinations) could improve sleep quality, duration, and deprivation in healthy subjects and patients, those who suffer from sleep-related issues. The current manuscript details the outcomes of EO-based treatments on the sleep quality of humans and the possible mechanisms associated with the health-promoting properties of EOs. Also, the toxicity and adverse effects of EOs have been discussed. The study indicated that EOs are potent adjuvant therapeutic candidates to manage mood-associated complications in humans. Moreover, the aromatherapeutic field requires detailed studies on toxicity and dose determination, which could provide safe and effective therapeutic results.
Keywords: aromatherapy